Conversion Therapy Versus Gay-Affirmative Therapy: Working With Ego-Dissonant Gay Clients - Kirby, Andrew (Auckland University of Technology, 2008)
This dissertation explores the issue of doing psychotherapy with ego-dissonant gay male clients. The methodology used is a modified systematic literature review with clinical illustrations. A dichotomy exists in the literature in relation to treating egodissonant gay clients who experience conflict between their sexuality and opposing values and beliefs. Each position tends to respond with a limited, exclusionary choice to either reject or accept one’s sexual orientation. This dissertation examines if there is a way to treat ego-dissonant clients without endorsing homophobic treatments or negating opposing values and beliefs. Freud’s views on homosexuality and sexual reorientation are delineated to inform and contextualise later writings on the subject. A review of conversion therapy and gay-affirmative therapy investigates the evidence of each, following which emerging integrative solutions are examined. Finally, a Kleinian model is proposed for individuals where neither a choice of a side nor comfortable resolution of the conflict seems feasible. While it is proposed that gay-affirmative therapy benefits the majority of ego-dissonant gay clients, this study recognises that each psychotherapeutic paradigm discussed caters, to some degree, to the uniquely different needs of individuals.
Keywords: Psychotherapy; Gays counselling; Homosexuality; Sexuality